Building Customer Loyalty Through Product Differentiation And Competitor Analysis: Evidence From A Natural Cosmetics MSME - Elfira Yunita Sapitri; Khaerul Muttakin; Subiyantoro (Universitas Islam Negeri Mataram, 2025)
The natural cosmetics industry faces intensifying competition as consumer awareness of product safety and environmental sustainability grows. This situation requires companies, especially micro, small, and medium enterprises (MSMEs), to develop marketing strategies that are not only sales-oriented but also focused on building customer loyalty as the foundation for business sustainability. This study aims to analyze efforts to increase customer loyalty at PT Karya Iwin Insani by examining product quality and service, and to strengthen competitive strategies through competitor analysis. The study employs a descriptive qualitative approach, collecting data through semi-structured interviews, non-participant observation, documentation, and a literature review. Informants were purposively selected from within the company who were directly involved in production, marketing, and customer service activities. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, and was tested for validity through source and technique triangulation. The results showed that customer loyalty was built through consistent quality of natural products, guaranteed safety of use, and environmental sustainability values internalized in the brand identity. In addition, the company used competitive analysis to develop product differentiation and value-based promotional strategies rather than relying on price competition. This strategy strengthens the company's market position and increases customer trust and loyalty. These findings indicate that the integration of customer loyalty building and competitor analysis plays an essential role in creating sustainable competitive advantage in the natural cosmetics industry.